The newspaper a escola and the construction of modern and republican school (laguna, decade of 1910) O jornal a escola e a construção da escola moderna e republicana (laguna, década de 1910) - Teive G.M.G.* (2013)
This study examines two copies of the newspaper The School, published by the School Group Jerônimo Coelho, Laguna, South of Santa Catarina in 1916. What would this newspaper have to do with those that years later were popularized by Decroly and Freinet and incorporated to Brazilian primary schools as part of the auxiliary school associations? This question was the thread of this historical reflection, seeking clues that would contribute to the discussion of active teaching, flagship of modern pedagogy, and active school, main feature of Progressive Education. Therefore, it analyzes the main themes debated by the newspaper The School such as: republican patriotism and bourgeois civility.